2020
DOI: 10.1038/s41541-020-00245-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine strategies for the Mtb/HIV copandemic

Abstract: One-third of world’s population is predicted to be infected with tuberculosis (TB). The resurgence of this deadly disease has been inflamed by comorbidity with human immunodeficiency virus (HIV). The risk of TB in people living with HIV (PLWH) is 15–22 times higher than people without HIV. Development of a single vaccine to combat both diseases is an ardent but tenable ambition. Studies have focused on the induction of specific humoral and cellular immune responses against HIV-1 following recombinant BCG (rBCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Thus, it is important to understand the driving forces behind chronic immune activation in a relevant coinfected preclinical model. This will lead to the discovery of key biomarkers predicting LTBI reactivation and therefore point the way to intervention strategies ( 13 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to understand the driving forces behind chronic immune activation in a relevant coinfected preclinical model. This will lead to the discovery of key biomarkers predicting LTBI reactivation and therefore point the way to intervention strategies ( 13 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of TB is increased in PLWH, even before CD4 + T cell counts decline significantly ( 74 ). Furthermore, active vaccination with BCG is contraindicated in PLWH due to the risk of dissemination ( 75 , 76 ), and combining antiretroviral regiments with TB chemotherapy can be challenging due to potential drug-drug interaction ( 77 ). Given the challenges of current treatment regimens and the lack of an effective prophylactic vaccine, exploring alternatives for TB control is crucial ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 HIVA immunogen, designed by Dr. Tomas Hanke, is composed of the full-length HIV-1 Gag protein combined with multiple CTL epitopes including P18I10 epitopes at the C-terminus [ 34 ]. The DNA, MVA and rBCG were selected as HIVA immunogen delivery vehicles and induced high magnitude and breadth of CTL epitope-specific cellular responses by using heterologous prime-boost regimes in mouse and non-human primate (NHP) models [ 34 , 101 ]. Our prior studies have shown that rBCG.HIVA prime in combination with MVA.HIVA boost elicited HIV-1-specific IFN-γ producing CD8+ T-cells in BALB/c mice [ 31 , 32 , 33 , 102 ].…”
Section: Discussionmentioning
confidence: 99%